Bismuth(III) Chloride Catalyzed Intramolecular Hetero-Diels–Alder Reaction: Access to cis-Fused Angular Hexahydrobenzo[c]acridines - Sabitha, Gowravaram; Shankaraiah, Kontham; Sindhu, Kancherla; Latha, Bejawada Madhavi (Synthesis, 2015)
New polycyclic hexahydrobenzo[c]acridines were synthesized in excellent yields by intramolecular [4+2]-cycloaddition reactions of aldimines derived from aromatic amines and 2-(4-methylpent-3-en-1-yl)benzaldehyde in acetonitrile in the presence of 10 mol% of bismuth(III) chloride. The reaction is highly diastereoselective, giving cis-fused benzoacridine derivatives preferentially.
Keywords: hetero-Diels–Alder reactions; catalysis; heterocycles; polycycles; aldimines; aldehydes